2017
DOI: 10.1002/smr.1851
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of design patterns on energy consumption

Abstract: Gang of Four (GoF) patterns are well‐known best practices for the design of object‐oriented systems. In this paper, we aim at empirically assessing their relationship to energy consumption, ie, a performance indicator that has recently attracted the attention of both researchers and practitioners. To achieve this goal, we investigate pattern‐participating methods (ie, those that play a role within the pattern) and compare their energy consumption to the consumption of functionally equivalent alternative (nonpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…They also concluded that neither prior exposure to design patterns nor prior exposure to the programming language was a significant factor. Feitosa et al [34] investigate the energy consumption on State/Strategy and Template Method on two open source software projects and compared their results to alternative solutions. Their results showed that alternative solutions use less energy in many cases.…”
Section: They Collected Data From 3 Open Source Software Projects (Jhmentioning
confidence: 99%
“…They also concluded that neither prior exposure to design patterns nor prior exposure to the programming language was a significant factor. Feitosa et al [34] investigate the energy consumption on State/Strategy and Template Method on two open source software projects and compared their results to alternative solutions. Their results showed that alternative solutions use less energy in many cases.…”
Section: They Collected Data From 3 Open Source Software Projects (Jhmentioning
confidence: 99%
“…Regarding energy consumption, we do not deem that adopting only energy consumption as dependent variable constitutes per se a prominent threat in our experiment. In addition, utilizing exclusively energy consumption measurements is a common practice in the field of software energy efficiency [15], [39]- [41]. However, relying on a specific tool to estimate the energy consumption (namely CodeCarbon), could have influenced the construct validity of our experiment.…”
Section: Construct Validitymentioning
confidence: 99%
“…The authors in [16] analyzed the effect of different well-known design patterns (e.g., Template Method, State, and Strategy) described in [17] on energy consumption and implemented alternative nonpattern solutions for comparison. Other approaches analyzed the impact of object-oriented programming features (e.g., polymorphism, inheritance, and operator overloading) and design patterns that use the features on energy efficiency while focusing on server systems [18] and embedded systems [19].…”
Section: Related Workmentioning
confidence: 99%